Increased metabolic variability in Korean patients with new onset bipolar disorder: a nationwide cohort study - Baek, Ji Hyun; Han, Kyungdo; Kim, Hyewon; Yang, Kyojin; Jeon, Hong Jin (Frontiers in Psychiatry, 2024)
The aim of this study was to determine associations between changes of metabolic parameters and the development of BD using nationally representative data. We used health examination data provided by the South Korean National Health Insurance System (NHIS) (n = 8,326,953). The variability of each metabolic parameter including weight circumference, blood pressure, fasting blood glucose, high-density lipoprotein cholesterol, and triglyceride levels was caculated using variability independent of mean (VIM) indices. The presence of metabolic syndrome was associated with new onset BD. Each metabolic parameter with high variability was associated with a higher risk of new onset BD compared to those with low variability after adjusting for age, sex, smoking, alcohol drinking, regular exercise, income status, baseline diabetes, hypertension, and dyslipidemia. As the number of highly variable metabolic parameters increased, the risk for new onset depression also increased even after covariates adjustment. The associations between new onset BD and metabolic variability were greater in populations with age > 50 years. In addition, these associations remained significant after adjusting for the presence of depression prior to diagnoses of BD. Our results suggest possibility of metabolic variability as an independent environmental risk factor for BD even after adjusting for the presence of metabolic syndrome.